A Long Limb Prediction, Body Mass Index, Flexibility and Speed to Long Jump Style Squatting - Abdurrachman, Abdurrachman (Department of Physical Education, Sport, Health and Recreation, 2018)
This study aims to determine the relationship and how much the prediction of long jump squat style achievement in terms of limb length, body mass index, body fleksibility and running speed. The objective of this research is that trained students of state senior high school in Pekalongan Regency, with a total sample of 60 students. The independent variables in this research is limb lenght, body mass index, body flexibility, and running speed whereas dependent variable was long jump with squat style achievement. This study uses multivariat correlational method. The results showed that the length of the legs, body and togok flexibility has a positive relationship, whereas the body mass index and running speed has a negative relationship with the long jump squat style achievement. Prediction value at limb length was 0.027, body mass index was -0.049, body flexibility was 0.026 and running speed was -0.234. The conclusion of this study is that there is a significant relationship and can be predicted between limb length, body mass index, body flexibility and running speed against long jump squat style achievement.